2022
DOI: 10.1128/mbio.01863-21
|View full text |Cite
|
Sign up to set email alerts
|

The Phenylacetic Acid Catabolic Pathway Regulates Antibiotic and Oxidative Stress Responses in Acinetobacter

Abstract: Acinetobacter baumannii causes a wide range of infections that are difficult to treat due to increasing rates of multidrug resistance; however, the mechanisms that this pathogen uses to respond to stress are poorly understood. Here, we describe a new mechanism of stress signaling in Acinetobacter that is mediated by the metabolite phenylacetic acid (PAA).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 66 publications
2
30
0
Order By: Relevance
“…Additionally, this downregulation occurs concomitantly with an upregulation of the whole paa phenylacetic acid degradation pathway (ABUW_2525–2536). Recent reports have shown a negative correlation between the paa and csu expression levels upon antibiotic treatment, thus linking phenylacetic acid levels to biofilm formation (Moon et al , 2017 ; Hooppaw et al , 2022 ). This result, together with the MBIC data for A. baumannii (Fig 2C ), suggests that biofilm inhibition in the presence of ace‐K is caused by the downregulation of the csu genes in a phenylacetic acid signalling‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, this downregulation occurs concomitantly with an upregulation of the whole paa phenylacetic acid degradation pathway (ABUW_2525–2536). Recent reports have shown a negative correlation between the paa and csu expression levels upon antibiotic treatment, thus linking phenylacetic acid levels to biofilm formation (Moon et al , 2017 ; Hooppaw et al , 2022 ). This result, together with the MBIC data for A. baumannii (Fig 2C ), suggests that biofilm inhibition in the presence of ace‐K is caused by the downregulation of the csu genes in a phenylacetic acid signalling‐dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…This anti‐biofilm effect appears to be mediated through the upregulation of the whole paa phenylacetic acid degradation pathway (ABUW_2525–2536). This pathway has been recently shown to significantly influence the expression of the csu operon and therefore biofilm levels (Moon et al , 2017 ; Hooppaw et al , 2022 ). In later experiments, we observed that ace‐K has a broad range of antimicrobial activity (Fig 5 ), ranging from a complete growth inhibition of S. maltophilia to no impact in S. aureus .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study provided more evidence that treatment with antibiotics at a subinhibitory concentration led to an approximately 7-fold increase in the expression of paaA and paaB to impact intracellular PAA levels in A. baumannii ( Hooppaw et al, 2022 ). They also reported that PAA catabolism is important for A. baumannii in multiple antibiotic stress conditions, especially in the presence of cytoplasmic targets such as ciprofloxacin, erythromycin, and tetracycline, where the biofilm formation ability is repressed in the WT strain but not impacted in a deletion mutant strain of paaB ( Hooppaw et al, 2022 ).…”
Section: Significance Of the Paa Pathwaymentioning
confidence: 99%
“…Biofilms are formed by A. baumannii on abiotic and biotic surfaces to survive in human serum and infection, resistance to desiccation stress, and starvation in the nosocomial environment ( Zeidler and Muller 2019 ). A recent study on the PAA pathway under antibiotic treatment in A. baumannii suggested that PAA could induce biofilm formation depending on the expression of Csu, a pili protein, which is one of the main determinants of biofilm formation ( Hooppaw et al, 2022 ). The exogenous addition of PAA can reverse the inhibition of Csu during antibiotic treatment ( Hooppaw et al, 2022 ).…”
Section: Significance Of the Paa Pathwaymentioning
confidence: 99%
See 1 more Smart Citation